Emotional Regulation and its Relationship with Decision-Making Ability among University Female Students in Saudi Arabia - Almotrefi, Norah (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية, 2025)
This study explores the relationship between emotion regulation and decision-making ability among female university students at an academic institution in Saudi Arabia. Emotional regulation plays a significant role in decision-making processes. Students who effectively manage their emotions are less likely to engage in risky behaviors and make impulsive decisions. Research shows that interventions aimed at enhancing emotional regulation skills can lead to better decision-making outcomes, particularly in high-stress situations typical of university life. This study has used the descriptive correlational approach, two scales were prepared for (1) emotional regulation, consisting of 45 statements across nine dimensions, and (2) decision-making ability, including 24 statements. The study tools were administered to 240 female students at the university. The research sample had a high degree of emotional regulation (average = 3.52, standard deviation = 0.24) and a higher degree of decision-making ability (average = 3.56, standard deviation = 0.53). Emotional regulation and decision-making ability did not differ significantly according to the independent variables of specialization and academic level. However, emotional regulation and decision-making ability had a significant positive correlation. The study concluded that universities should pay attention to providing counseling programs for university students to enhance their psychological and mental health. In addition, the relationship between emotional regulation and decision-making ability among university students is a significant area of research that has garnered attention due to its implications for mental health and academic performance. This framework can be understood through the dimensions of emotional regulation and decision-making ability. While the framework surrounding the relationship between emotional regulation and decision-making ability is established, significant gaps in longitudinal data, specific variable exploration, external influences, and practical applications remain in the study that could be addressed in future research.